2015
DOI: 10.4149/av_2015_02_179
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein prevents heavy metals overloading of cells and thus protects them against their toxicity

Abstract: Summary. -Physiological function of a prion protein (PrP) is not known yet. Regarding the relation of PrP to heavy metals it is known that PrP is able to bind divalent ions of copper, zinc, manganese and nickel through its octarepeat region. It has been hypothesized but not yet confirmed that PrP could play a role in copper metabolism. In this study, cells expressing human full-length PrP (HuPrP1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…370 It has been shown that the protein is involved in several cellular processes including neuroprotection against excitotoxicity and serum starvation, 371 proliferation and cell-cell adhesion, 370, 372 formation of synapses 373 and ligand binding. 374, 375 PrP can protect cells against heavy metal overloading and subsequent oxidative stress by binding divalent ions of copper, zinc, manganese and nickel. 375 Due to the ability of PrP to modulate cell proliferation and apoptosis it is believed to play a role on cancer development.…”
Section: Prions and Prion Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…370 It has been shown that the protein is involved in several cellular processes including neuroprotection against excitotoxicity and serum starvation, 371 proliferation and cell-cell adhesion, 370, 372 formation of synapses 373 and ligand binding. 374, 375 PrP can protect cells against heavy metal overloading and subsequent oxidative stress by binding divalent ions of copper, zinc, manganese and nickel. 375 Due to the ability of PrP to modulate cell proliferation and apoptosis it is believed to play a role on cancer development.…”
Section: Prions and Prion Diseasesmentioning
confidence: 99%
“…374, 375 PrP can protect cells against heavy metal overloading and subsequent oxidative stress by binding divalent ions of copper, zinc, manganese and nickel. 375 Due to the ability of PrP to modulate cell proliferation and apoptosis it is believed to play a role on cancer development. 376 Indeed, increased PrP C level has been found in gastric cancer, 377 colorectal cancer 378 and skin cancer.…”
Section: Prions and Prion Diseasesmentioning
confidence: 99%
“…In addition, PrP C is involved in copper transport and in cell defense mechanisms against oxidative insult, through the regulation of the intracellular CuZn superoxide dismutase activity (Cu-Zn SOD), protecting cells against heavy metals overload and subsequent oxidative stress [24,26]. Moreover, it has been suggested that overexpressed PrP C could be interpreted as a molecular marker of cell Cu deficiency [48, 49,50]. Thus, if morphine withdrawal promotes an increase of ROS molecules, we can hypothesize that enhanced expression of hippocampal PrP C may be considered as a phenomenon reflecting the ability of PrP C to link Cu 2+ and, in turn, to activate Cu-Zn SOD.…”
Section: Discussionmentioning
confidence: 99%